(3ZGjI GdShd aj Yde GdCUhds - (3YdGAGdOjf Ydj Hf eMeO NWGH GdHGLis; (3GdaNQ GdQGRj , GdaNQ GdQGRj,J (B606 (3g` s
(3ChdgG (B:s
(3gP eNJUQ ai CUhd Gdabg efJNH ef GdeMUhd s
(3BNQgG (B:s
(3Xf GdeDef dGjNWF s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3cTa GdXfhf (B- (3GdLRA (B2 - (3U (B1616 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1192s
Keywords: (3CUhd Gdabgs